The Middle-upper Devonian clastic wedge of the Franklinian geosyncline - Embry, Ashton F. (Ashton Fox) (University of Calgary, 1976)
Bibliography: p. 259-274. Middle - Upper Devonian elastic strata in the Canadian Arctic Islands are present over an area of about 200,000 sq km (75,000 sq miles) and are up to 5000 m (16,000 1) thick. The strata comprise a elastic wedge which was deposited in the Franklinian geosyncline prior to Late Devonian - Early Mississippian deformation. The elastic wedge is divided into eleven formations, and six facies are recognized within the strata. The formations and their facies content are: Blackley (submarine fan); Cape de Bray (marine slope); Weatherall (deltaic-marine shelf); Bird Fiord (open marine shelf and deltaic-marine shelf); Strathcona Fiord (meandering stream); Hecla Bay (braided stream); Fram (meandering stream); Hell Gate {braided stream); Nordstrand Point (meandering stream); Beverley Inlet (meandering stream); and Parry Islands (braided stream, meandering stream and deltaic-marine shelf). Mineralogy, facies distributions, paleocurrent patterns and regional geology all indicate that the source areas of the elastic strata lay to the north and east, and included the Caledonian and Pearya Mountain systems and Precambrian Shield of Greenland. Chert and rock fragments characterize detritus from the Pearya Mountains whereas detritus from the Caledonian Mountains and Precambrian Shield is characterized by a high percentage of monocrystalline quartz. Compositional variations within the elastic wedge indicate that the Pearya Mountains progressively supplied a higher proportion of the detritus throughout wedge development. Paleolatitude estimations, lithologies, fossils and clay minerailogy imply that the elastic wedge was deposited under humid tropical climatic conditions. Lithologic variations in fluvial strata suggest that the climate fluctuated between savanna and very humid. Clastic deposition commenced in the extreme northeast in Eifelian time, and a coastal plain prograded south and west until it covered almost the entire Arctic Islands area by Middle Frasnian. During progradation, submarine fan and ...